Organizational justice and work engagement with self-leadership as a mediating variable - Rino Adilla Putra; Okki Trinanda (Human Resource Management Studies, 2021)
The purpose of this study was to analyze: (1) The effect of organizational justice on work engagement for Grand Bunda Hotel Bukittinggi employees, (2) The effect of organizational justice on self-leadership among employees at Grand Bunda Hotel Bukittinggi, (3) The influence of self-leadership on work engagement among employees. Grand Bunda Hotel Bukittinggi, (4) The effect of organizational justice on work engagement with self-leadership as a mediating variable for employees of Grand Bunda Hotel Bukittinggi. The results showed that: (1) organizational justice has a positive and significant effect on work engagement of Grand Bunda Hotel Bukittinggi employees, (2) organizational justice has a positive and significant effect on self-leadership in Grand Bunda Hotel Bukittinggi employees, (3) the influence of self-leadership affects positive and significant towards work attachment to employees of Grand Bunda Hotel Bukittinggi, (4) self-leadership does not significantly mediate the relationship between organizational justice and work engagement for Grand Bunda Hotel Bukittinggi employees